(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper presents a 16-bit 100MS/s SAR ADC with 1V power supply for biomedical implant systems developed with low power technique i.e., DTMOS logic. It consists of a R-2R DAC, low-power comparator, a digital SAR logic with low-leakage. The designed comparator is a differential architecture that has used to have an excellent, common-mode noise rejection. Comparator was created for proper operation to remain in saturation and could be used with differential amplifier. The comparator is the chief block of power consumption, so we focused mainly much of ability we make to design this module. The ADC is designed using Cadence virtuoso with CMOS 45nm technology. For SFDR, SNR, ENOB and power consumption, the converter utilizes 63.97dB, 51.06 dB, 15.15 and 528.8uw.